Periodic Solutions of Neutral Fractional Differential Equations - Henriquez-Miranda, H (Wiley-VCH Verlag, 2017)
We characterize the existence of periodic solutions for some abstract neutral functional fractional differential equations with finite delay when the underlying space is a UMD space. © 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.